The Heuristic Significance of Art Sociology - Fitzi, Gregor (Simmel Studies)

(untitled) (Edizioni ETS, 2022)
Art sociology may be simply seen as a specialised domain of sociological research. Yet the article suggests that it has also an overarching diagnostic significance to gain a better understanding of ongoing societal transformation trends. It analyses the classical contribution of Weber, Simmel and Bourdieu to the topic. Weber develops a causal-historical explanation for the development of occidental music. It becomes a key to the interpretation of the specific occidental form of rationalism beyond religion and economy. Simmel has a different approach. Art is for him one of the expressions of the modern times that he wants to describe to understand the transformation of the society in which he lives. The diagnostic function of art is at the centre of interest. Bourdieu, on his side, proposes a historical reconstruction for the development of the intellectual field in France during the 19th century. In this frame, art contributes to a symbolic revolution that establishes autonomous societal fields and promotes a qualitative differentiation of complex societies. Yet, Bourdieu’s researches on art have also a diagnostic potential. Building on the analytical heritage of the classics, the article inquiries into the loss of autonomy of the art field in the contemporary art market and contributes to the debate on the heuristic significance of art sociology.